Religious Moderation in Indonesia’s Plural Space: A Perspective Inspired by Homi K. Bhabha - I Wayan Suasta (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
The development of interreligious studies has increasingly gained significant attention in global academic literature. However, most existing research still tends to focus on the dynamics of interreligious relations in Western countries. Theoretical and practical contributions from the Asian region—including the richness and complexity of its interreligious interactions—have not yet received adequate scholarly attention. This article aims to analyze interreligious relations in Indonesia by referring to field data collected through interviews with Muslim, Christian, and Kaharingan communities in the Central Kalimantan region. Using Homi K. Bhabha’s theoretical framework of the Third Space, this study highlights how interfaith interactions unfold among Islamic, Christian, and local Kaharingan communities in two villages: Pendahara and Tumbang Kalang, in the province of Central Kalimantan. This research explores how the narrative and practice of the third space emerge in interfaith relations, whether at the personal, institutional, or societal level. This study adopts a descriptive-qualitative approach with social-cognitive discourse analysis across three dimensions: micro, meso, and macro. The study’s findings indicate that the region’s diverse religious communities are capable of living peacefully side by side, strongly supported by the local socio-cultural context rich in heritage values. Cultural elements such as Indonesian-style communalism and a spirit of collectivity serve as key drivers in fostering harmonious interfaith relationships. The study concludes that these communities actively construct “third spaces”—shared spaces that allow for common ground in diversity, while still maintaining the uniqueness of each religious identity.